The Application of the Principle of Prudence in the Issuance of Replacement Certificates: A Perspective on Adat and Positive Law - Sianturi, Stefanus; Ramli, Asmarani (Faculty of Law Universitas Trunojoyo Madura, 2025)
This study aims to analyse the application of the principle of prudence in issuing replacement land certificates from both positive and customary law perspectives. It addresses the increasing land conflicts caused by duplicate certificates and administrative negligence in Indonesia’s land administration system. The research contributes a novel dual-legal approach by integrating statutory procedures and indigenous legal norms into a coherent framework to enhance legal certainty. Employing a normative juridical method, the study uses document analysis, statutory interpretation, and interviews with land officials. The primary data sources include Government Regulation No. 24 of 1997 and Decision No. 59/Pdt.G/2022/PN Unr. Findings reveal systemic weaknesses in verification procedures and a lack of institutional coordination, resulting in the fraudulent reissuance of certificates. Additionally, the neglect of adat-based verification undermines social legitimacy in customary regions. This research concludes that the current formal procedures are insufficient to prevent forgery and land conflicts. It recommends regulatory reform and the incorporation of community-based verification mechanisms as part of a precautionary legal standard. The study provides a critical foundation for integrating legal pluralism into national land governance.